Soil mesofauna amount and diversity by returning fresh and compost of crops biomass waste in ultisols in-situ: - Junita Barus; DIAN MEITHASARI; JAMALAM LUMBANRAJA; HAMIM SUDARSONO; KUSWANTA FUTAS HIDAYAT; DERMIYATI DERMIYATI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Barus J, Meithasari D, Lumbanraja J, Sudarsono H, Hidayat KF, Dermiyati. 2021. Soil mesofauna amount and diversity by returning fresh and compost of crops biomass waste in ultisols in-situ. Biodiversitas 21: 92-98. Newly added organic matter to the soil often has no significant effect on the physical and chemical properties of the soil. However, the addition of organic matter greatly affects the abundance and diversity of living organisms in the soil, because the addition of organic matter is one of the sources of food. The aim of this research was to study the impact of returning crop biomass waste in fresh or compost forms on the abundance and diversity of soil mesofauna. Three types of crop biomass residues (i.e. maize stover, rice straw, and soybean stover) were used at doses of 0, 2.5, 5.0, 7.5, and 10 t ha-1. Mesofauna observations were carried out three times, namely at two weeks after biomass waste application (before planting rice), at eight weeks (there were rice plants in the soil), and at fourteen weeks (after rice harvest). The soil sample for mesofauna observation was dry extracted using a Berlese funnel set up, and to calculate and identified using a binocular microscope. The result showed that the number and diversity of mesofauna in the addition of compost was higher than that of fresh biomass waste. Increasing the dose of biomass waste has an effect on increasing the number and diversity of soil mesofauna. The presence of rice plants in the soil at the time of observation also affected the abundance of soil mesofauna.